New Trends in Photodynamic Inactivation (PDI) Combating Biofilms in the Food Industry—A Review - Dan Wang (MDPI AG, 2021)
Biofilms cause problems in the food industry due to their persistence and incompetent hygiene processing technologies. Interest in photodynamic inactivation (PDI) for combating biofilms has increased in recent years. This technique can induce microbial cell death, reduce cell attachment, ruin biofilm biomolecules and eradicate structured biofilms without inducing microbial resistance. This review addresses microbial challenges posed by biofilms in food environments and highlights the advantages of PDI in preventing and eradicating microbial biofilm communities. Current findings of the antibiofilm efficiencies of this technique are summarized. Additionally, emphasis is given to its potential mechanisms and factors capable of influencing biofilm communities, as well as promising hurdle strategies.